Lipid trafficking between the endoplasmic reticulum and the chloroplast. (22nd May 2006) - Awai, K.; Xu, C.; Lu, B.; Benning, C.
Abstract : The photosynthetic (thylakoid) membrane of plants is one of the most extensive biological cell membrane systems found in Nature. It harbours the photosynthetic apparatus, which is essential to life on Earth as carbon dioxide is fixed and atmospheric oxygen released by photosynthesis. Lipid biosynthetic enzymes of different subcellular compartments participate in the biogenesis of the thylakoid membrane system. This process requires the extensive exchange of lipid precursors between the chloroplast and the ER (endoplasmic reticulum). The underlying lipid trafficking phenomena are not yet understood at the mechanistic level, but genetic mutants of the model plant Arabidopsis thaliana with disruptions in lipid trafficking between the ER and the chloroplast have recently become available. Their study has led to the identification of components of the lipid transfer machinery at the inner chloroplast envelope.